Totally real submanifolds in a quaternion space form - Bektas, M (Czechoslovak Mathematical Journal, 2004)
In this paper, we prove a theorem for n-dimensional totally real minimal submanifold immersed in quaternion space form.
Keywords: totally real submanifold; quaternion space form